LITERASI KEUANGAN DAN PERAN MEDIASI BIAS PERILAKU TERHADAP KEPUTUSAN INVESTASI INDIVIDU - Darmayanti, Ni Putu Ayu; Artini, Luh Gede Sri; Suryantini, Ni Putu Santi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.11.TAHUN.2023, 2023)
This research was conducted to find out the investment decision-making behavior of the younger generation, namely students who are members of the Investment Gallery of the Indonesia Stock Exchange. The importance of this research is related to the increasing role of students in investing in capital markets that are relatively risky so that they need to have an understanding of financial literacy and identify herding behavior biases and overconfidence in their investment decision making. The research was conducted on 135 students who were members of the Indonesia Stock Exchange Investment Gallery in several universities in Denpasar. The results of the data analysis showed that financial literacy and overconfidence had a positive effect on investment decisions, herding had a negative effect on investment decisions, financial literacy negatively affected herding behavior bias, but had a positive effect on overconfidence behavior bias while herding and overconfidence could mediate the relationship between financial literacy and investment decisions.